Distribution of the Phenotypic Effects of Random Homologous Recombination between Two Virus Species - Vuillaume, Florence; Thébaud, Gaël; Urbino, Cica; Forfert, Nadège; Granier, Martine; Froissart, Rémy; Blanc, Stéphane; Peterschmitt, Michel (PLoS pathogens, 2011)
Recombination has an evident impact on virus evolution and emergence of new pathotypes, and has generated an immense literature. However, the distribution of phenotypic effects caused by genome-wide random homologous recombination has never been formally investigated. Previous data on the subject have promoted the implicit view that most viral recombinant genomes are likely to be deleterious or lethal if the nucleotide identity of parental sequences is below 90%. We decided to challenge this view by creating a bank of near-random recombinants between two viral species of the genus Begomovirus (Family Geminiviridae) exhibiting 82% nucleotide identity, and by testing infectivity and in planta accumulation of recombinant clones randomly extracted from this bank. The bank was created by DNA-shuffling-a technology initially applied to the random shuffling of individual genes, and here implemented for the first time to shuffle full-length viral genomes. Together with our previously described system allowing the direct cloning of full-length infectious geminivirus genomes, it provided a unique opportunity to generate hundreds of "mosaic" virus genomes, directly testable for infectivity. A subset of 47 randomly chosen recombinants was sequenced, individually inoculated into tomato plants, and compared with the parental viruses. Surprisingly, our results showed that all recombinants were infectious and accumulated at levels comparable or intermediate to that of the parental clones. This indicates that, in our experimental system, despite the fact that the parental genomes differ by nearly 20%, lethal and/or large deleterious effects of recombination are very rare, in striking contrast to the common view that has emerged from previous studies published on other viruses.